Well-being of UiTM Shah Alam students living in off-campus environment / Muhammad Hilmy Muslim, Hafazah Abdul Karim and Ishak Che Abdullah. - Muslim, Muhammad Hilmy; Abdul Karim, Hafazah; Abdullah, Ishak Che (Universiti Teknologi MARA Cawangan Selangor, 2018)
Abstract This paper introduces a method to apply the principles of New Urbanism on an Egyptian neighborhood unit. It extends to their relationship with the common dimensions of urban design. It proposes four objectives: a) Interpret the new concepts of New Urbanism, b) Cite principles of Urbanism and trends emanating from it, c) Discover the structure of the philosophical concept of urbanization and d) Design a matrix inventories the compatibility of the principles of New Urbanism and urban design dimensions. Finally, the matrix tests the combination of the principles and the dimensions in a traditional Egyptian urban fabric, Basilica Church Plaza.